Analysis of Potential and Determination of Regional Tax Revenue Targets to Increase Regional Original Income in Bukittinggi City - Merry Lucyana; Sabri; Aulia Fauziah; Afrina Yenni; Dian Destria (PT. Gudang Pustaka Cendekia, 2025)
The research aims to analyze regional tax potential, the process of setting tax revenue targets, identifying factors that influence target achievement, strategies for increasing local revenue in Bukittinggi City. This research uses a descriptive qualitative approach with data collection techniques through documentation studies and in-depth interviews with informants from the Bukittinggi City Regional Financial Agency. The research results show that the tax potential in Bukittinggi City is very large, especially from the hotel and restaurant sector, but has not been fully explored optimally. Tax target setting is still fluctuating and does not fully reflect the real potential available. Factors that influence the success or achievement of targets include the level of taxpayer compliance, the quality of data collection, the tax administration system, as well as the influence of fiscal policy and local economic conditions. The optimization strategy implemented includes carrying out intensive outreach, developing a digital tax reporting system, updating and registering new data, as well as approaches that provide taxpayer education and awareness. This research recommends strengthening data, taking approaches with various agencies and maximizing tourism management to support a sustainable increase in Regional Original Income (PAD).